Analysis Of Arabic Language Sources on the History of the Local Rulers in the Struggle Against the Arab Caliphat Coination in the VII-VIII Centuries (Texas Journal of Philology, Culture and History, 2024)
In the article, the Arab caliphate in the VII-VIII centuries to the invasion against in the struggle local of rulers to history about Arabic tongue sources analysis will be done